Keeping Up with the Kardashians: Consumers' Intention to Engage in Cosmetic Surgery - Sood, Abhinav; Quintal, Vanessa; Phau, Ian (Routledge, 2017)
This study examined the predictors of intention to engage in a cosmetic surgery. A convenience sampling approach utilizing a self-administered pen-and-paper and online survey was used to collect 214 responses in Australia. Favorable attitude had a significant positive effect on intention to engage in a cosmetic procedure for female respondents. On the other hand, subjective norms had a significant positive effect on intention to engage in a cosmetic procedure for male respondents. Managerially, findings will help practitioners in the cosmetic surgery industry to implement marketing strategies that target this growing consumer segment.